2012
DOI: 10.1016/j.envpol.2011.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Long-term persistence of polychlorinated dibenzo-p-dioxins and dibenzofurans in air, soil and sediment around an abandoned pentachlorophenol factory in China

Abstract: a b s t r a c tAir, soils and sediments surrounding an abandoned pentachlorophenol (PCP) factory were sampled to determine the levels of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs), unintentionally formed during PCP production. The mean concentration of PCDD/Fs in ambient air was one order of magnitude higher than that of the reference site. A trend of decreasing concentrations with increasing distance from the factory was observed, suggesting this site has a significant influence on the regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The ambient air PCDD/PCDF concentrations can vary widely depending on the type of area investigated and on the presence of different emission sources, such as combustion activities (e.g., municipal waste incineration, hospital waste incineration, wood burning, forest fires), vehicle exhaust, metal smelting and processing sources, chemical manufacturing, biological and photochemical processes, and reservoir sources (soils, sediments, and treated wood) (O'Keefe et al, 1994;Kjeller and Rappe, 1995;Caserini and Monguzzi, 2002;McKay, 2002;Gullett and Touati, 2003;Lee et al, 2004;Tame et al, 2007;Hsu et al, 2011;Li et al, 2012). After the PCDD/PCDF release into the atmosphere the compounds are dispersed throughout the environment matrices (e.g., soil and/or waters) by atmospheric transport.…”
Section: Introductionmentioning
confidence: 99%
“…The ambient air PCDD/PCDF concentrations can vary widely depending on the type of area investigated and on the presence of different emission sources, such as combustion activities (e.g., municipal waste incineration, hospital waste incineration, wood burning, forest fires), vehicle exhaust, metal smelting and processing sources, chemical manufacturing, biological and photochemical processes, and reservoir sources (soils, sediments, and treated wood) (O'Keefe et al, 1994;Kjeller and Rappe, 1995;Caserini and Monguzzi, 2002;McKay, 2002;Gullett and Touati, 2003;Lee et al, 2004;Tame et al, 2007;Hsu et al, 2011;Li et al, 2012). After the PCDD/PCDF release into the atmosphere the compounds are dispersed throughout the environment matrices (e.g., soil and/or waters) by atmospheric transport.…”
Section: Introductionmentioning
confidence: 99%
“…Polychlorinated dibenzo‐ p ‐dioxins (PCDDs) are a group of highly hazardous chemical compounds that are produced during the incineration of municipal and medical wastes and as by‐products of certain industrial processes (Czuczwa & Hites, 1984; Kumagai, Koda, & Oda, 2003; Li et al, 2012). They are also released into the environment during volcanic eruptions and forest fires (Prange, Gaus, Weber, Papke, & Muller, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, iron sintering (Liu et al, 2013b) and metal production processes cause the formation and emission of PCDD/Fs as well as dl-PCBs (Ba et al, 2009a,b). Studies have shown that atmospheric concentrations of PCDD/Fs and dl-PCBs at industrial (Li et al, 2012;Die et al, 2015) and urban (Deng et al, 2011;Li et al, 2014) areas are higher than those at rural areas (Thuan et al, 2013;Shih et al, 2006).…”
Section: Introductionmentioning
confidence: 99%